Discuss Jordanian Legal Consistency to Apply IFRS: 13 Fair Value Measurement -ASE case study - Abdullah Ibrahim NAZAL; Ahmad MAKHLOUF (Journal of North African Economies, 2025)
The study concentrates on discuss Jordanian legal consistency to apply IFRS: (13) by study ASE case. It gives legal model to follow Jordanian legal environment impact on ASE screen. Searchers used the descriptive inductive method by study the law resources in order to find Ignorance, deception, unfair price, and ASE solving problems. Searchers classified it by levels to show ASE cases as monitor or activator or punisher. The searchers found that: Legal Consistency can accept IFRS 13 as standard for listed companies in ASE because of concentrating on essential data without details, but, ASE is not efficiency to give IFRS (13) the fair value in level (1) and IFRS cannot impact all listed companies to become in same efficiency, while it not links pricing with the real price in the real market as gambling to activate speculation and weaken using measurement.